2012
DOI: 10.1039/c1dt10698h
|View full text |Cite
|
Sign up to set email alerts
|

Near-UV to red-emitting charged bis-cyclometallated iridium(iii) complexes for light-emitting electrochemical cells

Abstract: Herein we report a series of charged iridium complexes emitting from near-UV to red using carbene-based N^C: ancillary ligands. Synthesis, photophysical and electrochemical properties of this series are described in detail together with X-ray crystal structures. Density Functional Theory calculations show that the emission originates from the cyclometallated main ligand, in contrast to commonly designed charged complexes using bidentate N^N ancillary ligands, where the emission originates from the ancillary N^… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
118
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 123 publications
(130 citation statements)
references
References 62 publications
12
118
0
Order By: Relevance
“…Similar results have been recently reported by Kessler et al, who synthesized a series of Ir-iTMCs emitting from near-UV to red using a neutral pyridine-carbene ancillary ligand and different cyclometalating ligands (e.g., 22, Figure 19). [121] The low PLQYs observed for these complexes were ascribed to non-radiative process through the population of 3 MC states. Nevertheless, LECs with emission from the bluish-green to orange region of the visible spectrum were fabricated.…”
Section: Ir-itmcs Based On Strong-field Ancillary Ligandsmentioning
confidence: 97%
See 1 more Smart Citation
“…Similar results have been recently reported by Kessler et al, who synthesized a series of Ir-iTMCs emitting from near-UV to red using a neutral pyridine-carbene ancillary ligand and different cyclometalating ligands (e.g., 22, Figure 19). [121] The low PLQYs observed for these complexes were ascribed to non-radiative process through the population of 3 MC states. Nevertheless, LECs with emission from the bluish-green to orange region of the visible spectrum were fabricated.…”
Section: Ir-itmcs Based On Strong-field Ancillary Ligandsmentioning
confidence: 97%
“…[117] A new approach, based on the use of carbene-type ligands, was recently introduced by Yang et al [85] They demonstrated that the combination of methyl-or n-butylsubstituted bisimidazolium carbene-type ligands together with the dfppyH cyclometalating ligand yields blue LECs Figure 19) to cover the whole visible spectrum. [121] For instance, devices with complex 22 and its fluorinated version (i.e., complex with fluoro groups in the cyclometalating ligand) show blue-green emissions at 544 and 512 nm, respectively. However, high voltages (6 V) are needed to obtain moderate luminance values (20 cd m À2 ).…”
Section: Blue Lecsmentioning
confidence: 99%
“…As a matter of fact, despite huge efforts, stable blue LECs based on iridium(III) complexes are still missing. 9,10,[25][26][27] This is related to their intrinsic degradation via the metal-centered (MC) states, which are not present in copper(I) complexes. 28 As such, much more stable blue devices are expected by using the latter.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, with the experimental data of Table 1 the radiative rate constant (k r ) and non-radiative rate constant (k nr ) were calculated. 24,25 Complex 1 shows a high value of k nr , which is consistent with the low QY and electrochemical gaps but, according to the energy gap law, is inconsistent with the higher energy of emission. 30,31,7 Consequently, it is possible to consider the possibility of a non-emitting state of lower energy, that the same time would be preventing the ISC.…”
Section: Electrochemical and Photophysical Propertiesmentioning
confidence: 60%
“…k r = QY/τ and k nr = 1/τ-k r . 24,25 In Table 1 the electrochemical data are reported vs the Fc + /Fc couple and correspond to the oxidation process of Ir 3+/4+ , at positive potentials, and the reduction process of the ancillary ligand, at negative potential, as can be observed for another d 6 low spin complexes. 26 These values can be related with the energies of the highest-occupied molecular orbital (HOMO) and lowest-unoccupied molecular orbital (LUMO).…”
Section: Electrochemical and Photophysical Propertiesmentioning
confidence: 99%